ESG as a nonmarket strategy to cope with geopolitical tension: Empirical evidence from multinationals' ESG performance - Kim, Jin Hyung; Kwak, Jooyoung; Park, Hyung‐Kun (Strategic Management Journal, 2025)
Abstract Research Summary Although rising geopolitical tension is critically affecting multinational enterprises (MNEs), our understanding of geopolitics and its effects on corporate strategy is surprisingly limited. This study sheds light on this underexplored topic by examining the environmental, social, and governance (ESG) strategy of foreign MNEs amid tension between their home and host countries. We argue that the media plays a critical role in shaping host‐country public perceptions of such tension. As media‐reported tension increases, foreign MNEs enhance their subsidiaries' ESG performance to alleviate potential institutional pressure from the host‐country public. We further show that historical conflicts positively moderate this relationship, whereas ongoing conflicts serve as a scope condition that diminishes this relationship. This manifests that MNEs attempt to maximize ESG's insurance‐like benefits in coping with geopolitics. Managerial Summary Rising geopolitical tension leading to a less stable global business environment highlights the growing importance of geopolitics and strategic responses of firms. This study explores how host‐country media coverage of geopolitical tension affects foreign MNEs. If host‐country news media reports more tense interactions between MNE's home and host countries, the MNE ex ante is likely to experience heightened pressure from the host‐country public. Thus, we argue and show that MNEs subject to pressure from the host‐country public intensify their ESG efforts to enjoy the insurance‐like benefits of ESG's prosocial initiatives. Our study also shows that both past and ongoing conflicts between home and host countries differentially influence MNE's ESG efforts because the anticipated effectiveness of their strategy is heterogeneous.